(untitled) (E Conference Zone, 2022)
This article reviews the composition of owners and the legal framework for the activities of limited companies formed from joint-stock companies in Uzbekistan. The review reveals that as a result of privatization in practice, large investors have accumulated controlling shares in Uzbek limited companies. Moreover, it was suggested that an effective structure of ownership must be formed to ensure adequate corporate governance.